Switching control of a hypersonic vehicle based on guardian maps. (May 2016) - Xiao, Dibo; Liu, Mengying; Liu, Yanbin; Lu, Yuping
Abstract: For the air-breathing hypersonic vehicles (AHSV) with a broad flight envelope, this paper proposes a new controller design method to ensure robust stability in the presence of external disturbances. The proposed method is based on the guardian maps theory and H ∞ Linear Parameter Varying (LPV) technique. In this paper, an LPV model of the AHSV is firstly established using the Jacobian linearization method. By incorporating the guardian maps theory and H ∞ technique, a set of controllers is designed such that the closed loop poles lie in the desired area. The major merit of the proposed method is that all controller parameters over the overall flight envelope can be automatically determined in the iterative courses that are started from an arbitrary initial point within the flight envelope. Finally, the proposed approach is demonstrated by an illustrative example. The results show that the designed controller is operated to stabilize the air-breathing hypersonic vehicle over a wide flight envelope, and to exhibit satisfactory tracking performance as well as strong robustness. Highlights: A novel controller using the guardian maps is developed for the hypersonic vehicle. The control parameters are automatically obtained in the expected stability region. The switching control is realized by smoothly changing the obtained parameters. Global stability and strong robustness are guaranteed over the large flight envelope.